Analisis Pengaruh Pendidikan Kewirausahaan, Sosio Demografi, Kemampuan Dan Self Efficacy Terhadap Minat Berwirausaha (Studi Mahasiswa Fakultas Ekonomi Universitas Pekalongan) - Dian Milasari (Jurnal Ekonomi Dan Bisnis, 2017)
Indonesia as a developing country still has problems in terms of unemployment. BPS data says that open unemployment in 2016 as many as 7,024,172 people. Based on that fact, entrepreneurship has an important role in alleviating unemployment and improving country's economy. McCleeland in Silvia (2013) states that a country can advance if 2% of the total population is an entrepreneur. The purpose of this study is to determine whether there is a positive influence either simultaneously or partially between the socio-demographic variables, ability and self efficacy to entrepreneurship interests (Case Study of College Student Faculty of Economics, University of Pekalongan) 2016/2017 academic year. This research is a sample research with Accidental Sampling technique using 100 respondents. Data collecting method was done by questionnaire method which then processed using quantitative analysis method consisting of validity test, reliability test, autocorrelation test, classical assumption test, and statistical test of t and F. The result of analysis showed that entrepreneurship education, socio demography, ability and self efficacy have influence on entrepreneurship interests either simultaneously or partially.